Zinc about it – zinc and calf immunity - Kesler, Kathryn W.; Abuelo, Angel (Frontiers in Immunology, 2024)
Micronutrients, such as vitamins and trace minerals, are critical for supporting growth, performance, health and maintaining redox balance. Zinc (Zn), an essential micronutrient, aids the functioning of innate and adaptive immune cells. This scoping review aims to assemble and evaluate the evidence available for the role of Zn within calf immunity. Relevant literature was identified within Web of Science, PubMed, and CABI using search terms specific to the major innate and adaptive immune cell populations. There was no evidence that Zn supplementation altered neutrophil, natural killer cell, or T-cell functions. However, there was limited evidence to support Zn supplementation with reduced monocyte numbers, but there was no evidence to associate the monocytopenia with improvements in monocyte function. There is moderate evidence to suggest that Zn supplementation was beneficial for maintaining epithelial barriers of integumental and mucosal surfaces. The evidence supports supplementation above the current industry recommendations for improving immunoglobulin (Ig) production, with the strongest results being observed for IgG and IgM. Moreover, Zn supplementation was associated with reduced proinflammatory cytokine production, which may reduce inflammation-associated hypophagia and warrants further investigation. Furthermore, Zn reduced the duration of clinical signs in animals facing respiratory disease and diarrhea. However, consensus is needed about the optimal dose, route, and Zn formulation most appropriate for supporting immunity. In conclusion, while the literature supports that Zn could enhance calf immunity, there is insufficient evidence to adequately determine the extent to which Zn impacts innate immune cell and T-cell functions. Determination of the immune cell functions susceptible to modification by Zn supplementation is an important knowledge gap for enhancing the understanding of Zn and calf immunity.